The Effect of Celebrity Endorser and Brand Image on Purchasing Decision for Honda Vario Motorcycle at Astra Motor Tais in Seluma Regency - Rina Romanda Sari; Siti Hanila; Rina Trisna Yanti (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the effect of celebrity endorser and brand image simultaneously on purchasing decisions for a Honda Vario motorcycle at Astra Motor Tais in Seluma Regency. The samples in this study were 35 consumers who purchased a Vario motorcycle at Astra Motor Tais in Seluma Regency. The data were collected using a questionnaire and the analytical methods used were multiple linear regression, determination test and hypothesis testing. Based on the calculation of multiple linear regression equation, it showed that X1 (celebrity endorser) and X2 (brand image) have an effect on purchasing decisions (Y), with the results of the regression test: Y = 9.070 + 0.414X1 + 0.387 X2. This means that when there is an increase in the use of celebrity endorsers then the purchasing decision will also increase, and when the brand image then the purchasing decision will also increase.The coefficient of determination of the R square is 0.508. This means that celebrity endorser (X1) and brand image (X2) have an effect on purchasing decisions for a Honda Vario motorcycle (Y) by 54.4%, while the remaining 45.6% is influenced by other variables not examined in this study. Based on the test results with the t test, the hypothesis is made to prove there is an effect. The test results for variable X1 (celebrity endorser) show a significance value of 0.013 <0.05. Because the significance value is less than 0.05, then X1 (celebrity endorser) has a significant effect on purchasing decisions (Y). The variable X2 (brand image) shows a significance value of 0.020 <0.05. Because the significance value is less than 0.05, then X2 (brand image) has a significant effect on purchasing decisions (Y). Based on the results of hypothesis testing with the F test, a significance value of 0.000 <0.05 and a significance level below 0.05 indicates that the celebrity endorser (X1) and brand image (X2)) have a positive and significant effect on purchasing decisions (Y).